Rural households’ livelihood vulnerability to climate variability and extremes: a livelihood zone-based approach in the Northeastern Highlands of Ethiopia - Mekonen, Abebe Arega; Berlie, Arega Bazezew (Ecological processes, 2021)
Background The adverse effects of climate variability and extremes exert increasing pressure on rural farm households whose livelihoods are dependent on nature. However, integrated and area-specific vulnerability assessments in Ethiopia in general and the study area, in particular, are scarce and insufficient for policy implications. Therefore, this study aims to quantify, map, classify, and prioritize the level of vulnerability in terms of the components of exposure, sensitivity, and adaptive capacity in the Northeastern Highlands of Ethiopia. The study area is divided into six livelihood zones, namely, Abay-Beshilo Basin (ABB), South Wollo and Oromia eastern lowland sorghum and cattle (SWS), Chefa Valley (CHV), Meher-Belg , Belg , and Meher. A total of 361 sample households were selected using proportional probability sampling techniques. Survey questionnaire, key informant interview, and focus group discussions were used to collect the necessary data. Rainfall and temperature data were also used. Following the IPCC’s climate change vulnerability assessment approach, the climate vulnerability index (CVI) framework of Sullivan and Meigh’s model was used to assess the relative vulnerability of livelihoods of rural households. Twenty-four vulnerability indicators were identified for exposure, sensitivity, and adaptive capacity components. In this regard, Iyengar and Sudarshan’s unequal weighting system was applied to assign a weight to indicators. Results The results revealed that Belg and Meher were found to be the highest exposure livelihood zones to vulnerability with an aggregated value of 0.71. Equally, SWS, ABB, Belg , and CHV livelihood zones showed moderate level of sensitivity to vulnerability with an aggregated value between 0.45 and 0.60. The study noted that livelihood zone of Belg (0.75) was found to be at high level of livelihood vulnerability. ABB (0.57) and CHV (0.45) were at a moderate level of livelihood vulnerability while Meher-Belg (0.22) was the least vulnerable livelihood zone due to a high level of adaptive capacity such as infrastructure, asset accumulation, and social networks. Conclusion It was identified that disparities of livelihood vulnerability levels of rural households were detected across the study livelihood zones due to differences in the interaction of exposure, sensitivity, and adaptive capacity components. The highest levels of exposure and sensitivity combined with low level of adaptive capacity have increased households’ livelihood vulnerability. More importantly, the biophysical and socioeconomic sensitivity to livelihood vulnerability were exacerbated by slope/topography, soil erodibility, and population pressure. Therefore, designing livelihood zone-based identifiable adaptation strategies are essential to reduce the exposure and sensitivity of crop-livestock mixed agricultural systems to climate calamity.